The AMS Weather Book: The Ultimate Guide to Americas Weather - Williams, Jack. (American Meteorological Society : Imprint: American Meteorological Society, 2009)
America has one of the most varied and dynamic weather systems in the world. Every year, the Gulf Coast is battered by hurricanes, the Great Plains are ravaged by tornados, the Midwest is pummeled by blizzards, and the temperature in the Southwest reaches a sweltering 120 degrees. Extreme weather can be a matter of life and death, but even when it is pleasant72 degrees and sunnyweather is still central to the lives of all Americans. Indeed, its hard to imagine a topic of greater collective interest. Whether we want to know if we should close the storm shutters or just carry an umbrella to work, we turn to forecasts. But few of us really understand the science behind them. All that changes with The AMS Weather Book. The most comprehensive and up-to-date guide to our weather and our atmosphere, it is the ultimate resource for anyone who wants to understand how hurricanes form, why tornados twirl, or even why the sky is cerulean blue. Written by esteemed science journalist and former USA Today weather editor Jack Williams, The AMS Weather Book covers everything from daily weather patterns to air pollution and global warming and explores the stories of people coping with severe weather and those who devote their lives to understanding the atmosphere, oceans, and climate. Words alone, of course, are not adequate to explain many meteorological concepts, so The AMS Weather Book is filled with engaging full-color graphics that explain such concepts as why winds blow in a particular direction, how Doppler weather radar works, what happens inside hurricanes, how clouds create wind and snow, and whats really affecting the earths climate. For Weather Channel junkies, amateur meteorologists, and storm chasers alike, The AMS Weather Book is an invaluable tool for anyone who wants to better understand how weather works and how it affects our lives.